059 Pharmacodynamics of rituximab on B cells in paediatric patients with immune disorders. (December 2018) - Pan, S; Yu, H; Surti, A; Cheng, I; Marks, S; Brogan, P; Eleftheriou, D; Standing, J
Abstract : Background: Rituximab is a chimeric IgG-1 monoclonal antibody that depletes B cells, aiding in the treatment of several conditions including autoimmune and immunodeficiency diseases. It is not licensed for use in children but administered off-label. The current study aimed to identify the pharmacodynamics of rituximab in children with immune disorders in order to optimise the dosing regimen. Methods: Electronic data of children prescribed with rituximab at Great Ormond Street Hospital, London, United Kingdom were collected from a retrospective and anonymised study. Two intravenous infusions of rituximab, each at a dose of 750 mg/m 2 with a maximum dose of 1000 mg, were given at day 1 and 15 within 6 months. Plasma concentrations of rituximab were not available. CD19 +B cell counts were measured before and after rituximab treatment. A turnover model was constructed in NONMEM (version 7.3) to describe the life cycle of CD19 +B cells considering the effect of rituximab on increasing the death rate of CD19 +B cells. Rituximab was assumed to be eliminated by first-order kinetics. Results: 296 measurements of CD19 +B cell counts were collected from 46 children with 13 different immune diseases. The 2-compartment model well described the time course of CD19 +B cells following rituximab administration. The elimination half-life of rituximab and CD19 +B cells were estimated to be 18 and 40 days, respectively; these findings were consistent with that reported from the literature. ?Methotrexate and cyclophosphamide were found to increase the killing effect by 62% and 33%, respectively. Other covariates such as age and gender were not found significant. Conclusions: The findings from the current study will be used to establish dosing regimens of rituximab for treating children with immune diseases.